Design and Implementation of eTansiyon Mobile Software Application [ETansiyon Mobil Yazilim Uygulamasinin Tasarim ve Gerçekleştirimi] - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2020)
In this study, a mobile application called eTansyion designed and developed for global disease hypertension, which affects the whole world, can be used by both patients and doctors to follow their health status. In this study, the components of the eTansiyon mobile application are presented and the stages of the Rapid Application Development approach used in the development process are explained. eTansiyon is an application where patients can record, monitor their measured blood pressure data, create graphics of this data and share with their doctors on iOS and Android platforms. Especially in an epidemic period, it is expected that the developed application will contribute to this research field by offering a model based on the common approach of medicine and computer science. © 2020 IEEE.
Keywords: Health Software; hypertension; Mobile Health